The Effects of Plant Breeders’ Rights on Wheat Productivity and Varietal Improvement in South African Agriculture - Charity Ruramai Nhemachena (Sustainability, 2019)
The strengthening of the intellectual property rights (IPRs) for plant varieties provide incentives for breeding companies to invest more resources in plant breeding. The main objective of this paper was to analyze the effects of strengthening the wheat variety intellectual protection on wheat productivity and the release of new varieties. The strength of IPR systems was measured using an intellectual property (IP) protection index, and plant breeders’ rights (PBRs) granted for wheat varieties. The empirical analyses were based on correlation and multiple regression analyses. The results showed that strengthening IPR systems in South Africa contribute to improving wheat productivity and increasing the number of wheat varieties released. Furthermore, although the robust coefficients of the other IPR variables are positive, they are statistically insignificant for all scenarios. There is a need for more incentives beyond granting PBRs and strengthening of IPR systems to be provided in the whole wheat sector to stimulate increased investments and the release of new varieties.